2018
DOI: 10.1038/s41418-018-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

BH3-only proteins are dispensable for apoptosis induced by pharmacological inhibition of both MCL-1 and BCL-XL

Abstract: The impressive selectivity and efficacy of BH3 mimetics for treating cancer has largely been limited to BCL-2 dependent hematological malignancies. Most solid tumors depend on other anti-apoptotic proteins, including MCL-1, for survival. The recent description of S63845 as the first specific and potent MCL-1 inhibitor represents an important therapeutic advance, since MCL-1 is not targeted by the currently available BH3 mimetics, Navitoclax or Venetoclax, and is commonly associated with chemoresistance. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 38 publications
10
44
1
Order By: Relevance
“…A previous study, however, convincingly demonstrated that NOXA-triggered release of BIM from MCL-1 was essential for BAX/BAK activation 44 . Our results resemble findings from another study that showed dispensability of BIM (and other BH3-only proteins) for apoptosis induction when MCL-1 and BCL-XL are inhibited 5 . Whether attenuated cytotoxicity of NaCl/WEHI-539 in PUMA-deficient cells indicates involvement of PUMA in hypertonicity-enforced BCL-XL addiction requires further studies (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A previous study, however, convincingly demonstrated that NOXA-triggered release of BIM from MCL-1 was essential for BAX/BAK activation 44 . Our results resemble findings from another study that showed dispensability of BIM (and other BH3-only proteins) for apoptosis induction when MCL-1 and BCL-XL are inhibited 5 . Whether attenuated cytotoxicity of NaCl/WEHI-539 in PUMA-deficient cells indicates involvement of PUMA in hypertonicity-enforced BCL-XL addiction requires further studies (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3a). BAX is essential for MOMP in HCT116 cells and its activation is controlled by interaction with MCL-1 and BCL-XL 5,22,23 . Coimmunoprecipitation experiments, however, failed to demonstrate hypertonicity-induced changes of BCL-XL/MCL-1 interaction with BAX ( Fig.…”
Section: Noxa Upregulation Is Critical For Hypertonicity-enforced Bclmentioning
confidence: 99%
See 1 more Smart Citation
“…In a CRC cell line HCT116, treatment with A-1155463 alone was sufficient to induce apoptosis, while MCL-1 inhibitor S63845 alone did not induce any apoptosis. However, combining the two compounds resulted in more pronounced apoptosis even in the absence of all BH3-only proteins, in a BAX dependent manner [171].…”
Section: Bh3 Mimetics For Crc Therapymentioning
confidence: 95%
“…Cells that express high level of NOXA either basally or induced by other therapies show increased sensitivity to BCL-XL inhibition by A-1155463 and ABT-737 [119,169]. This suggests that concurrent treatment with MCL-1 inhibitors might potentiate the effect of BCL-XL inhibition in tumors that either present with high MCL-1 or low NOXA levels [170,171]. In a CRC cell line HCT116, treatment with A-1155463 alone was sufficient to induce apoptosis, while MCL-1 inhibitor S63845 alone did not induce any apoptosis.…”
Section: Bh3 Mimetics For Crc Therapymentioning
confidence: 99%